Determining optimal surge arrester’s location in distribution network - Quyen, Huy Ánh; Nguyen, Phan Thanh; Nguyen, Công Tráng (Journal of Technical Education Science, 2010)
To protect the distribution substation from lightning overvoltage, the lightning arrester is installed at the high voltage side of transformers. The determination of reasonable distance between lightning arrester and terminals transformer to efficiently protect the transformer and switching devices of the substations is very necessary. This paper presents a new method for calculating the separated distance and the Mean Time Between Failure (MTBF) of the transformer with different configurations to assure the life of transformer according to given requirement and with consideration of the affected factors such as the shielding factor of the object, areas ground flash density, and the inductance value of connected wires. The OPSOLA program is built to help the users to easily determine the appropriate installed position of lightning arrester and check MTBF for the existing configuration of substation.